Fabrication of binder-free ultrafine WC-6CO composites by coupled multi-physical fields activation technology - Huang, Kunlan; Qin, Yi; Yin, Deqiang; Yang, Yi; Yang, Gang (Cranfield University Press, 2013)
A novel sintering method, named as coupled multi-physical fields activation technology, has been introduced for the forming of various material powder systems. Compared with the conventional ones, this technique presents more advantages: lower sintering temperature, shorter forming time, and remarkable inhibition of the grains coarsening. In the study, the cylinders of Φ4.0mm×4.0mm had been formed with ultrafine WC-6Co powders. The relative properties of sintered WC-6Co cemented carbides, such as hardness and the microstructures, had been obtained. The study has shown that a relative density, 97.80%, of the formed samples, could been achieved when the case of temperature 850℃, heating rate 50℃/s, pressure 75MPa and Electro-heating loop 6 times, were used. More importantly, the circumscription for the growth of grain size of WC, attributed to the effect of electrical field, renders coupled multi-physical fields activation technology applicable for getting WC-6Co cemented carbides with fine grain size and good properties.
Keywords: Microstructures; Ultrafine WC-6Co powders; Coupled Multi-physical Fields Activation